A Review of Government Programs on Job Creation and Skills Improvement in Indonesia - Nugroho, Dr. Agus Eko; Andadari, Roos Kities (Pusat Penelitian Ekonomi-LIPI, 2015)
This study investigates various government programs within ten ministries/institutions that implement the programs for employment creation and skills improvement for the poor and vulnerable in Indonesia. The methodology used in the study is based on qualitative analysis, emphasizing the relevance, affectivity, sustainability and impact of the programs on job creation and skills improvement for the poor and vulnerable. The study has reviewed 35 programs encompassing 182 activities and 293 sub-activities. From these programs, ten most relevant programs are selected for further analysis in terms of their implementation and potential impact on job creation and skills improvement for the poor/vulnerable. The two main conclusions are raised in the study. Firstly, the ten programs investigated are relevant in terms of having a potential to create long- term employment and improve skills for the poor/vulnerable. Yet, most programs have not specified key performance indicators (KPI). Secondly, among the ten programs, the program for improving government capacity in providing service to migrant workers in Pillar 1, the program of Sekolah Lapang (SLPTT program) in Pillar 2 and the apprenticeship (magang) program in Pillar 3 can be be scaled up as they are very relevant in terms of targeted recipient and their potential impact to job creation and skills improvement for the poor/vulnerable.